A Technical Survey on Delay Defects in Nanoscale Digital VLSI Circuits - Prathiba Muthukrishnan; Sivanantham Sathasivam (Applied Sciences, 2022)
As technology scales down, digital VLSI circuits are prone to many manufacturing defects. These defects may result in functional and delay-related circuit failures. The number of test escapes grows when technology is downscaled. Small delay defects (SDDs) and hidden delay defects (HDDs) are of critical importance in industries today since they are the source of most test escapes and reliability problems. Improving test quality and creating new test methods, algorithms, and test designs requires a comprehensive study of these delay defects. This article reviews the effect and impact of SDD and HDD in logic circuits. It also analyzes the relevant fault models, automatic test pattern generation (ATPG) methods, faster-than-at-speed testing (FAST), cell-aware (CA) based delay tests, test quality metrics, diagnosis of SDDs and HDDs, and commercially available Electronic Design Automation (EDA) tools. Based on the analysis, the benefits and drawbacks of several accessible approaches are addressed.